The IJHPR's growing scientific impact - Bruce Rosen; Stephen C. Schoenbaum; Avi Israeli (BMC, 2018)
Abstract The Israel Journal of Health Policy Research (IJHPR) was launched in 2012, with a mission that included fostering intensive intellectual interactions among health policy scholars in Israel and abroad. Now, as the journal approaches the end of its seventh year of publication, we can all be proud that this component of our mission is increasingly being realized. As of the end of November 2018, the Web of Science included 404 articles published by the IJHPR. These IJHPR articles had generated 1023 citations via 847 citing articles. Just over 70% of those citing articles were in journals other than the IJHPR, with the vast majority of those being in non-Israeli journals. The authors of the citing articles were most often based in institutions in the US (35%), Israel (33%), England (9%) or Canada (7%). Looking to the future, we hope that the IJHPR will receive even more submissions from authors based in Israel or other countries that are well-designed data-based studies; thoughtful, comprehensive policy analyses; or important integrations of a body of knowledge. In all instances, these should be relevant to Israeli health policy and health care. We hope that many, ideally most, will also be relevant to scholars, policymakers and professionals in other countries.